Effects of salicylic acid, zinc and glycine betaine on morpho-physiological growth and yield of maize under drought stress - Ramadan Shemi (Nature Portfolio, 2021)
Abstract Drought is one of the major environmental stresses that negatively affect the maize (Zea mays L.) growth and production throughout the world. Foliar applications of plant growth regulators, micronutrients or osmoprotectants for stimulating drought-tolerance in plants have been intensively reported. A controlled pot experiment was conducted to study the relative efficacy of salicylic acid (SA), zinc (Zn), and glycine betaine (GB) foliar applications on morphology, chlorophyll contents, relative water content (RWC), gas-exchange attributes, activities of antioxidant enzymes, accumulations of reactive oxygen species (ROS) and osmolytes, and yield attributes of maize plants exposed to two soil water conditions (85% field capacity: well-watered, 50% field capacity: drought stress) during critical growth stages. Drought stress significantly reduced the morphological parameters, yield and its components, RWC, chlorophyll contents, and gas-exchange parameters except for intercellular CO2 concentration, compared with well water conditions. However, the foliar applications considerably enhanced all the above parameters under drought. Drought stress significantly (p < 0.05) increased the hydrogen peroxide and superoxide anion contents, and enhanced the lipid peroxidation rate measured in terms of malonaldehyde (MDA) content. However, ROS and MDA contents were substantially decreased by foliar applications under drought stress. Antioxidant enzymes activity, proline content, and the soluble sugar were increased by foliar treatments under both well-watered and drought-stressed conditions. Overall, the application of GB was the most effective among all compounds to enhance the drought tolerance in maize through reduced levels of ROS, increased activities of antioxidant enzymes and higher accumulation of osmolytes contents.